Pengaruh Online Customer Review dan Online Customer Rating terhadap Keputusan Pembelian melalui Marketplace Shopee (Studi Kasus pada Mahasiswa Aktif Prodi Manajemen Angkatan 2017 UNP Kediri) - Al Aradatin, Sulton Ali; Muslih, Basthoumi; Meilina, Restin (Universitas Nusantara PGRI Kediri, 2021)
Significant technological developments in recent years have had an impact on people's behavioral styles in shopping in this modern era, it is easier for people to get what they need, many marketplaces have emerged in Indonesia, one of which is Shopee which is well-known among people. According to data collected by katadata.com Shopee was ranked first in the largest site visitors in the third quarter of 2020, reaching 96.5 million in 2018. This is due to the many reviews and ratings on shopee products that attract people to make purchases through the shopee marketplace. Many research prove that online customer reviews and online customer ratings have a relationship with customer purchase interest and become one of the important features, but not a factor that causes increased customer trust. Therefore, online marketplace companies must make reviews and ratings as one of the main marketing tools that can increase company revenue. Currently, Indonesian consumers are more interested in the use of media. This study is an active student of the 2017 UNP Kediri Management Study Program. The number of samples used in this study was 30 respondents. The analysis technique used is multiple linear regression by considering the classical assumption test requirements which include normality test, multicollinearity test, heteroscedasticity test and autocracy test. Hypothesis testing used t-statistical test to test the effect partially and F-statistics to test the effect simultaneously. The results of this study indicate that partially and also simultaneously the online customer review and online customer rating variables have a significant effect on purchasing decisions. Keywords: Online customer review, online customer rating, and purchasing decisions.